Seasonal epidemiology of ticks and aspects of cowdriosis in N'Dama village cattle in the Central Guinea savannah of Cote d'Ivoire - Knopf, L; Komoin-Oka, C; Betschart, Bruno; Jongejan, Frans; Gottstein, Bruno; Zinsstag, Jacob (My University, 2002)
In the Central Guinea savannah of Cote d'Ivoire, cattle breeding started only similar to30 years ago. The impact of parasitism on the overall health status and productivity of the trypanotolerant N'Dama cattle in this area is unknown. In close collaboration with national veterinary institutions and local farmers, we studied spectrum, burden and seasonal dynamics of ticks (including aspects of cow-driosis) on N'Dama village cattle. In a longitudinal study, three randomly selected cattle herds (traditional farming type) of one village were examined repeatedly for ticks. Spectrum, burden, seasonal epidemiology of ticks were assessed. In these traditional herds (which lack (ecto)parasite management), all animals were infested by ticks at monthly counts. Five different tick species were identified; the four genera in order of frequency were: Amblyomma (overall prevalence 96%), Boophilus (47%), Hyalomina (
Keywords: N'Dama cattle; ticks; tick-borne diseases; Cote d'Ivoire; cowdriosis; AFRICAN CATTLE; ZEBU CATTLE; SUSCEPTIBILITY; INFESTATION; RUMINANTS; GAMBIA; ACARI